2020
DOI: 10.1175/jas-d-19-0224.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bulk Mass Flux Formulation Using Large-Eddy Simulations

Abstract: In this study, bulk mass flux formulations for turbulent fluxes are evaluated for shallow and deep convection using large-eddy simulation data. The bulk mass flux approximation neglects two sources of variability: the interobject variability due to differences between the average properties of different cloud objects, and the intraobject variability due to perturbations within each cloud object. Using a simple cloud–environment decomposition, the interobject and intraobject contributions to the heat flux are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…It must therefore be parameterized with a different approach. Our findings support a treatment for pressure drag that should take as its starting point for multiple drafts with different strengths, as in the “core‐cloak” conceptual model of Gu et al (2016a) for example. A recent theoretical study (Yano, 2020) also suggests that the inhomogeneity of vertical velocity must be introduced in the plume model; otherwise, the buoyancy and entrainment effect will perfectly cancel out with the counterbalancing force from the pressure, leaving a pure drag force to prevent a steady state solution.…”
Section: Discussion and Summarysupporting
confidence: 80%
See 3 more Smart Citations
“…It must therefore be parameterized with a different approach. Our findings support a treatment for pressure drag that should take as its starting point for multiple drafts with different strengths, as in the “core‐cloak” conceptual model of Gu et al (2016a) for example. A recent theoretical study (Yano, 2020) also suggests that the inhomogeneity of vertical velocity must be introduced in the plume model; otherwise, the buoyancy and entrainment effect will perfectly cancel out with the counterbalancing force from the pressure, leaving a pure drag force to prevent a steady state solution.…”
Section: Discussion and Summarysupporting
confidence: 80%
“…The Smagorinsky‐Lilly scheme (Lilly, 1962; Smagorinsky, 1963) is used for the parameterization of subgrid turbulence. Further details of the model configuration can be found in Gu et al (2020). Our analyses cover a period of equilibrium from Hour 5 to Hour 6 of the simulation, with 1 min output frequency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, for parameterization purposes, it is the mean vertical velocity of a cloud that is often needed, rather than the velocity at updraft center. Furthermore, a recent study (Gu et al, 2020) found that a partitioning into the mean velocities of the "core" and "cloak," namely, the strong and weak parts of the updrafts respectively, can significantly improve the representation of vertical transport in a simple bulk transport equation. This indicates the importance of predicting vertical velocities in different parts of clouds and thus the need for a better understanding of pressure drag, not only in the cloud center but also off the central axis.…”
Section: Introductionmentioning
confidence: 99%